Anesthesia strategies for elderly patients with craniocerebral injury due to foreign-body penetration in the plateau region: a case report - Sun, Yongtao; Liu, Yang; Liu, Peng; Zhang, Min; Liu, Mengjie; Wang, Yuelan (Frontiers in Medicine, 2024)
The administration of anesthesia for elderly individuals who are critically ill, suffering from severe craniocerebral injuries, and living in plateau regions presents a rare, intricate, and highrisk challenge. This case study outlines the specific anesthesia management protocols necessary for plateau-dwelling patients with significant craniocerebral damage undergoing prolonged invasive procedures.Case report: A 76-year-old male patient had a 26-year history of foreign body penetration of the skull and had experienced local purulent discharge and pain for the previous 20 days. The diagnoses included right hypoplasia, a foreign body in the skull with an infection, hypokalemia, hypoproteinemia, pulmonary fibrous foci, and bilateral pleural effusion. For almost six months, the patient suffered from recurring headaches, blurred vision, and sluggish bodily movement. The patient had a poor diet, poor sleep quality, normal urination, and no noticeable weight loss since the onset of the illness. The right anterior ear had a 2 cm skin abscess with yellow pus and a black metal foreign body tip. The left eyelid was red and swollen and the left conjunctiva was hyperemic; the right eyelid showed no abnormalitys, and both pupils were wide and round, with light and adjustment reflexes and no cyanosis on the lips.Skull development was normal. No dry or moist rales were audible in either lung. The heart rhythm was regular and the heart rate was 50 BPM. Chest CT revealed left lung calcification foci, bilateral pleural effusion, and fiber foci in the lower lobes of both lungs.Furthermore, the patient in question was of advanced age and had a complex medical history, including prolonged exposure to high altitudes and previous instances of severe craniocerebral trauma, among other uncommon pathophysiological characteristics. Notably, the patient also underwent surgical interventions at both high and low altitudes, adding to the complexity of their case. To ensure patient safety, close multidisciplinary collaboration, the development of a precise surgical plan, and the implementation of a suitable perioperative anesthetic management strategy are imperative.